Miniaturized Raman instrumentation detects carotenoids in Mars-analogue rocks from the Mojave and Atacama deserts - Vítek, P; Jehlička, J; Edwards, H G M; Hutchinson, I; Ascaso, C; Wierzchos, J (Philosophical transactions. Series A, Mathematical, physical, and engineering sciences, 2014)
This study is primarily focused on proving the potential of miniaturized Raman systems to detect any biomolecular and mineral signal in natural geobiological samples that are relevant for future application of the technique within astrobiologically aimed missions on Mars. A series of evaporites of varying composition and origin from two extremely dry deserts were studied, namely Atacama and Mojave. The samples represent both dry evaporitic deposits and recent evaporitic efflorescences from hypersaline brines. The samples comprise halite and different types of sulfates and carbonates. The samples were analysed in two different ways: (i) directly as untreated rocks and (ii) as homogenized powders. Two excitation wavelengths of miniaturized Raman spectrometers were compared: 532 and 785 nm. The potential to detect carotenoids as biomarkers on Mars compared with the potential detection of carbonaceous matter using miniaturized instrumentation is discussed.
Keywords: algae; pigments; portable Raman; salt; halophile; cyanobacteria